(untitled) (American Journal of Agricultural Science, Engineering, and Technology, 2023)
Poor weed control automatically results in yield losses, and the review has provided a range of 30-100% depending on the crop, weed species, and stage of the crop. The timing and efficacy of the methods matter. Across the region, farmers use different methods broadly grouped into preventive, cultural, and curative methods. Herbicide application, a form of curative method, is seen as an effective means of weed control, which is cheap, time, and labor-saving technology for adoption. Also, the technology helps in soil carbon sequestration. Hence, it could be used to improve crop productivity and profitability of already of the farming systems in the region. The current adoption of herbicides is very low across SSA, ranging from 0.1-55%. The low adoptions in SSA could be associated with low education levels, poor knowledge, and experience with technology, cultural beliefs, high poverty levels, small farm size, and weak government and intercountry policies and extension services.